2014
DOI: 10.1371/journal.pone.0110262
|View full text |Cite
|
Sign up to set email alerts
|

Help Seeking Behavior of Women with Self-Discovered Breast Cancer Symptoms: A Meta-Ethnographic Synthesis of Patient Delay

Abstract: Background and ObjectivePatient delay makes a critical contribution to late diagnosis and poor survival in cases of breast cancer. Identifying the factors that influence patient delay could provide information for adopting strategies that shorten this delay. The aim of this meta-ethnography was to synthesize existing qualitative evidence in order to gain a new understanding of help seeking behavior in women with self-discovered breast cancer symptoms and to determine the factors that influence patient delay. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
100
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(110 citation statements)
references
References 58 publications
(270 reference statements)
6
100
0
4
Order By: Relevance
“…This is consistent with findings from a review of pathology reports that nearly half of Malawian breast cancer patients experienced multiple symptoms for over 1 year before being diagnosed [29]. Symptom appraisal and cancer knowledge have been cited as factors of delay and cancer behaviors in studies worldwide [8, 9, 13, 20]. Other studies from low- and middle-income countries outside of Africa support these findings, especially that perceiving symptoms as non-threatening can delay diagnosis [12, 30].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This is consistent with findings from a review of pathology reports that nearly half of Malawian breast cancer patients experienced multiple symptoms for over 1 year before being diagnosed [29]. Symptom appraisal and cancer knowledge have been cited as factors of delay and cancer behaviors in studies worldwide [8, 9, 13, 20]. Other studies from low- and middle-income countries outside of Africa support these findings, especially that perceiving symptoms as non-threatening can delay diagnosis [12, 30].…”
Section: Discussionsupporting
confidence: 85%
“…However, few studies from Africa, where health resources are scarce, cancer awareness is low, and screening is uncommon, have been conducted or included in such reviews. Previous qualitative studies are largely descriptive, and few developed conceptual models to understand the complex factors influencing delayed and early detection [10, 12, 13]. Additionally, few delay models have explored the influence of alternative treatments and traditional medicine, which are commonly used among cancer patients across Africa [14].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, studies among breast cancer patients in Egypt and Malawi found that informational and emotional support and social networks more generally were important influences on patients’ health‐seeking decisions and behaviors . Symptom disclosure was often linked with timely health‐seeking in a metaethnographic synthesis of breast cancer delay studies , which is similar to our finding that social support facilitated faster cancer care patterns. Therefore, information, education, and communication strategies should target the general population to increase awareness broadly and leverage communication and relationships through social networks.…”
Section: Discussionsupporting
confidence: 85%
“…Many sociodemographic factors such as age, low socioeconomic status, area of residence, and appraisal of health services may be associated with some women delaying seeking medical consultation (Kannan & Veazie, 2015; Khakbazan, Taghipour, Latifnejad Roudsari, & Mohammadi, 2014; Robinson, Christensen, Ottesen, & Krasnik, 2011). Several factors associated with help-seeking delay include psychological factors such as: lack of awareness and knowledge of the disease, disease beliefs, treatment beliefs, and emotional distress (Iskandarsyah et al, 2014).…”
Section: Beliefs About Pain Controlmentioning
confidence: 99%